LA RELATION ENSEIGNANT – ELÈVE / ETUDIANT DANS LE CADRE DU PROCESSUS INSTRUCTIF-ÉDUCATIF D’ÉDUCATION MUSICALE - Constantina BOGHICI (Studia Universitatis Babeş-Bolyai. Musica)
After an experience of over 40 years of musical education, acquired in musical schools and high schools, and, during the last 18 years, in higher education institutions, we would like to bring to light a few principles that inspired us in our work with the pupils and with the students. From the very beginning, we considered that the relation between educator and educated is essential when carrying out the teaching activity in the artistic domain. The few failures we recorded were caused by external causes, unrelated to the teaching process: the lack of native talent as far as the pupil/student was concerned, the family’s lack of interest for the artistic aspects, defectological elements, poor health, etc. In the age of the modern communication means, the relation teacher-student has acquired new meanings: the educator needs to master the new technologies, to use his/her musical knowledge and techniques in order to highlight teaching strategies focused on the interests, preferences and aptitudes of the person who is being educated. The principles of modern teaching promote a democratic relationship, of learning through cooperation, which motivates and captivates the pupil’s/student’s attention for study, getting him/her to discover by himself/herself patterns and methods of solving different musical problems. To conclude, a positive attitude, based on modern teaching techniques, will determine the pupil/student to have a rigorous school trajectory, focused on performance and implicitly on professional musical success.